Global Supply Chain Management: Navigating Challenges and Opportunities in a Post-Pandemic World - M. Manikandan, M. Murugan, Karthick R, Sethupathy K (Journal of Informatics Education and Research, 2024)
The COVID-19 crisis has revealed weaknesses in worldwide supply networks and led companies to revise their plans for resilience and flexibility. The research assesses the tactics needed to reduce disruptions in the “supply chain” over both long and short periods. We identified crucial areas such as sourcing and procurement and logistics and storage that require change using the Grey-DEMATEL method. Analysis reveals that implementing advanced technologies including autonomous vehicles and Big Data Analytics can greatly increase adaptability and risk control. By forming partnerships with Third Party Logistics providers (TPLs) and adopting multi-channel distribution networks companies increase customer satisfaction and manage demand more effectively. This research highlights the necessity of moving from a cost-oriented “supply chain” approach towards one that emphasizes resilience and flexibility. Future studies must examine the combination of sustainability techniques with cutting-edge risk management models to boost international “supply chain” effectiveness.